Study of Iron Deficiency Anemia in Patients with Low Hemoglobin Level Attending Birat Medical College Teaching Hospital, Nepal - Sinha, Amrita; Singh, Mrinalini; Sedhain, Sapana; Bhattarai, Soorya (Birat Journal of Health Sciences, 2025)
Introduction: Despite nutritional advancements and iron fortification programs, anemia remains the top global health burden for decades. Serum ferritin level is one of the important adjunct diagnostic method for the diagnosis of iron deficiency anemia. Objective: To study the prevalence of iron deficiency anemia in anemic patient, to categorise the different types of anemia based on peripheral blood smear findings and to observe serum ferritin level in all anemic patients. Methodology: This was a hospital based prospective cross-sectional study carried out in Birat Medical College Teaching Hospital where 350 anemic patients were included. All anemic patients of either sex, aged 20 years or older, and had hemoglobin levels below normal for their respective sexes were included for the study. Similarly children under twenty years old who were anemic and patients with blood cancers (acute or chronic leukemia) were excluded. Results: Out of 350 anemic patients, the overall prevalence of iron deficiency anemia in anemic patient was found to be 37.1% based on serum ferritin level. According to the morphology of cells on peripheral blood smear, it was seen that 183 (52.2% ) patients had microcytic hypochromic anemia, 33.4% had normocytic normochromic anemia and 14.3% patient had macrocytic anemia. Similarly iron deficiency anemia was found to be more common in females (38.6%) than in male patients (34.4%) with 21-30 years age group most commonly affected. Conclusion: Microcytic hypochromic anemia was the most common morphological type of anemia with the iron deficiency anemia being the commonest one based on serum ferritin level.